2012
DOI: 10.1097/mpg.0b013e31823315d1
|View full text |Cite
|
Sign up to set email alerts
|

Liprotamase Long‐term Safety and Support of Nutritional Status in Pancreatic‐insufficient Cystic Fibrosis

Abstract: Treatment with a mean of 5.5 capsules of liprotamase per day, during meals and snacks, for up to 12 months was safe, well tolerated, and associated with age-appropriate growth and weight gain or weight maintenance in subjects with CF-related EPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
(40 reference statements)
1
16
0
3
Order By: Relevance
“…Changes in other nutritional parameters such as triglycerides were not seen. In clinical intervention studies in patients with CF and PEI, 1 showed improvements in total serum cholesterol, HDL and serum vitamins A and E after~30e44 days on PERT [51], whereas another found no clinically significant changes in albumin, prealbumin, fasting triglycerides, cholesterol or fat-soluble vitamins over 1 year of PERT [74]. However, it has to be taken into account that the patients participating in these trials were not required to be PERT-naïve and had received PERT prior to study entry.…”
Section: Nutritional Parameters For Monitoring Treatment Effect Of Pertmentioning
confidence: 93%
See 2 more Smart Citations
“…Changes in other nutritional parameters such as triglycerides were not seen. In clinical intervention studies in patients with CF and PEI, 1 showed improvements in total serum cholesterol, HDL and serum vitamins A and E after~30e44 days on PERT [51], whereas another found no clinically significant changes in albumin, prealbumin, fasting triglycerides, cholesterol or fat-soluble vitamins over 1 year of PERT [74]. However, it has to be taken into account that the patients participating in these trials were not required to be PERT-naïve and had received PERT prior to study entry.…”
Section: Nutritional Parameters For Monitoring Treatment Effect Of Pertmentioning
confidence: 93%
“…Some have reported significantly lower mean concentrations versus healthy controls [73] whereas others reported values within normal ranges in patients on PERT [74] and higher than normal values in 48% of patients on PERT and vitamin supplements [75].…”
Section: Vitamin Ementioning
confidence: 96%
See 1 more Smart Citation
“…Liprotamase is a non-porcine pancreatic enzyme-replacement product that contains three different microbially derived and biotechnology-produced enzymes. Liprotamase appeared to be well tolerated in phase III studies, and the coefficient of fat absorption improved by 10 % compared with placebo [85,86]. However, in 2011, the US FDA questioned the evidence for efficacy of liprotamase and asked for further clinical studies before an approval for use could be granted; a further phase III study is now planned (NCT02279498).…”
Section: Pancreatic Enzymesmentioning
confidence: 88%
“…Although long-term benefits of ivacftor in children (6-11 years of age), adolescent and adult patients with G551D mutations were presented at the conference (up to 96 weeks) [4][5][6], many questions remain including its role and safety in very young children (<6 years) and its role in the treatment of patients with other related ('gating' or class III) mutations. Studies to address these questions are about to commence in the USA and Europe.…”
mentioning
confidence: 99%